No Condition is Permanent : Middle Class in Nigeria in the Last Decade - Corral, Paul; Molini, Vasco; Oseni, Gbemisola (World Bank Group, Washington, DC, 2015)
The economic debate on existence and definition of the middle class has become particularly lively in many developing countries. Despite this growing interest, the identification of the middle class group in these countries remains quite challenging. Building on a recently developed framework to define the middle class, this paper tries to estimate the Nigerian middle class size in a rigorous quantitative manner. By exploiting publicly available panel data, the expenditure associated to a 10 percent probability of falling into poverty is estimated, and this is used as the middle class threshold for Nigeria. The threshold expenditure for the middle class in Nigeria is found to be 378.39 Naira per capita per day (2010 PPP). Relying on this threshold and through survey-to-survey imputation the size of Nigeria's middle class in 2003 is also estimated. The results show that there has been considerable improvement on the size of the middle class and poverty reduction between 2003 and 2013. Poverty decreased between 2003 and 2013 from 45 to 33 percent, while the middle class increased from 13 percent to 19 percent. Nevertheless the results still paint a heterogeneous picture of poverty and the middle class in Nigeria, where the largest portion of the population, although above the poverty threshold, continues to live with average or high vulnerability to poverty.